(2,9-Dimethyl-1,10-phenanthroline-κ(2) N,N′)bis(thiocyanato-κS)mercury(II) - Warad, Ismail (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, [Hg(SCN)(2)(C(14)H(12)N(2))], contains two complex molecules in which the Hg(II) atoms are both four-coordinated in a distorted tetrahedral configuration by two N atoms from a chelating 2,9-dimethyl-1,10-phenanthroline ligand and by two S atoms from two thiocyanate anions. The 1,10-phenanthroline ligand is slightly folded for one complex, the dihedral angle between the pyridine planes being 5.3 (1)°. In contrast it is nearly planar [0.5 (1)°] as it complexes with the other Hg(II) atom. The thiocyanate ligands are virtually linear and the S atom is bonded to Hg(II) with N⋯S—Hg angles ranging from 99.3 (1) to 103.5 (1)°. Despite the presence of six aromatic rings in the asymmetric unit, there are no significant intermolecular π–π contacts between phenanthroline ligands as the centroid–centroid distance of the closest contact between six-membered rings is 4.11 (1) A°.